'Fit' for change: measuring designer competence. Issue 3 (2nd October 2018) - Leclerc, Rémi; Horan, Roy
Abstract: A deeper understanding of designers' core competencies and psychological traits supports both design education and more effective integration of design into industries seeking innovation. The Integral Psychological Profile, an instrumental breakthrough in psychometric testing, measured a group of young designers for core competence and trait 'fit, ' or 'compatibility, ' to various design curricula. Psychological 'fit' was significantly associated with better academic performance. Creativity, exploration, and proactivity emerged as gatekeepers to design proficiency with additional competency alignment reinforcing success. IPsP traits, found in high performers, closely matched previous attempts at defining designer attributes. A more comprehensive model of designer competence was developed. Findings also illumined some key psychological guidelines for advancing design in business.